A qualitative study on the real experience of discharging patients with urinary catheter placement after radical prostatectomy - LIU Yuping; GAI Qiongyan; ZHONG Weiqin; LI Ping (Yixue xinzhi zazhi)
Objective To explore the real experiences of patients discharged with indwelling urinary catheters after radical prostatectomy, and to propose targeted nursing interventions and continuous care recommendations.Methods A purposive sampling method was used to select patients who underwent radical prostatectomy discharged from a urology department at Nanjing Drum Tower Hospital in Nanjing from June 2023 to October 2023. Data were collected through in-depth interviews and analyzed using NVivo 12.0 software and the Colaizzi 7-step analysis method for qualitative research.Results There were 3 themes and 8 sub-themes summarized from the interviews, including physiological discomfort and daily life challenges (limited daily activities, disrupted sleep, and challenges with clothing and personal hygiene), psychological stress and social difficulties (social stigma, social avoidance), social support and rehabilitation guidance (needs for family daily care support, needs for love and respect, rehabilitation guidance needs).Conclusion Patients undergoing radical prostatectomy with indwelling urinary catheters face complex lifestyle challenges after discharge. Therefore, developing a comprehensive rehabilitation nursing plan for radical prostatectomy patients after discharge is advised to ensure that patients receive continuous care and support to enhance overall quality of life, thus promoting their physical, mental, and social recovery.